1983
DOI: 10.1203/00006450-198308000-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Atrial Pacing-Induced Tachycardia on Left Ventricular Contractile Function in Conscious Newborn and Adult Sheep

Abstract: SummaryIn order to determine if an increase in heart rate is associated with an increase of left ventricular contractile function during the neonatal period we recorded phasic and mean aortic blood pressure. left atrial mean or left ventricular end diastolic Dressure. phasic left ventricular blood pressure, aortic blood flow velocity and the instantaneous first derivatives of left ventricular blood pressure (dP/dt) and aortic blood flow velocity (dV/dt) during pacing-induced tachycardia in conscious newborn an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…This is similar to what we found in untreated newborn pigs in which baseline heart rate ranged between 130 and 150 beatslmin, and any increase in heart rate beyond that point would contribute very little to the contractile state. Our results differ from those of a previous study done on conscious neonatal lambs (29). This study demonstrated a substantial increase in LV contractility during rapid atrial pacing.…”
Section: Discussioncontrasting
confidence: 57%
“…This is similar to what we found in untreated newborn pigs in which baseline heart rate ranged between 130 and 150 beatslmin, and any increase in heart rate beyond that point would contribute very little to the contractile state. Our results differ from those of a previous study done on conscious neonatal lambs (29). This study demonstrated a substantial increase in LV contractility during rapid atrial pacing.…”
Section: Discussioncontrasting
confidence: 57%
“…Treatment differences in cardiac output must be explained by changes in either heart rate, contractility, preload, or afterload (14). The increased heart rate in chloralose-treated lambs was within the range associated with increased cardiac output and contractility in conscious lambs tested by electrical pacing of the left atrium (15). The heart rate increase in chloralose-treated lambs would be expected to increase cardiac output; therefore, heart rate changes alone do not explain the reduced cardiac output.…”
Section: Pulmonary Vascular Resistancementioning
confidence: 87%
“…These changes were unrelated to baseline tone of the circulation, cardiac output, mean left atrial pressure, or physiologically important changes in arterial blood gas tensions. In addition, chloralose-treated lambs had increased heart rate, systemic vascular resistance, and pulmonary vascular resistance compared to controls during alveolar hypoxia (13)(14)(15). Importantly, chloralose-treated lambs did not increase their cardiac output during alveolar hypoxia a s did control lambs.…”
mentioning
confidence: 85%
“…Fisher and Gross (27) have shown that pacing the newborn lamb heart at rates up to 300 bpm caused no significant increase in left atrial or left ventricular end diastolic pressure. It is more likely that the left atrial hypertension seen at high rates of infusion resulted from the markedly elevated systemic vascular resistance (i.e.…”
Section: Effects Of Dopumine Infusionmentioning
confidence: 99%